Direct-acting antivirals: the endgame for hepatitis C? - D’Ambrosio, Roberta; Degasperi, Elisabetta; Colombo, Massimo; Aghemo, Alessio (Current opinion in virology, 2017)
•DAAs for HCV treatment include protease (NS3/4A) inhibitors, RNA-dependent polymerase (NS5B) inhibitors and NS5A inhibitors.•The combination of DAA owning to different classes have led to high SVR rates, independently on HCV genotype and fibrosis stage.•Treatment duration and RBV use depend from HCV genotype, liver disease and treatment history; 12 weeks without RBV is most common schedule.•IFN-free regimens have allowed treating previous IFN-contraindicated patients, such as decompensated and solid-transplanted organ patients. Directly-acting antivirals (DAA) have finally allowed all patients to be potentially cured from chronic hepatitis C (HCV) infection. All-oral, Interferon (IFN)-free regimens are based upon the combination of molecules targeting different sites of the HCV replication process. Three classes of DAA exist: protease inhibitors (anti-NS3/4A), RNA-dependent polymerase inhibitors (anti-NS5B) and anti-NS5A inhibitors, which are characterized by different antiviral potency and barrier to resistance and therefore are usually combined in different treatment schedules. Treatment regimens are still largely dependent on HCV genotype and stage of liver disease, with duration ranging between 12 weeks and 24 weeks, while overall treatment efficacy has climbed to nearly 95% in most patient groups, including historically difficult-to-treat categories (HCV genotype 1, advanced liver disease). The elimination of IFN has allowed safe and efficacious treatment of patients formerly contraindicated to antiviral therapy, such as decompensated cirrhosis and solid organ transplant recipients. Availability of potent and safe antiviral drugs combined with improvement of worldwide access to treatment could finally lead to HCV elimination in the next decades.